'An instruction in good citizenship': scouting and the historical geographies of citizenship education. Issue 1 (4th April 2012) - Mills, Sarah
<x xml:space="preserve">Abstract</x> This paper examines informal citizenship training for youth and the historical geographies of education over time through analysing the Scout Movement in Britain and its activities in the first half of the twentieth century. In doing so, it highlights the complexity of youth citizenship and the significance of non‐school spaces in civil society to our understandings of young people's positioning as citizen‐subjects. Drawing on archival research, I demonstrate how a specific youth citizenship project was constructed and maintained through the Scout Movement. I argue that various processes, strategies and regulations were involved in envisioning 'citizen‐scout' and developing both duty‐bound, self‐regulated individuals as well as a wider collective body of British youth. This analysis speaks to broader debates on citizenship, nationhood and youth, as well as highlighting how the historical geographies of citizenship education are an important area of study for geographers.